Relationship between parasitic Margaritifera margaritifera larvae and the host fish, Atlantic salmon - Nagahawatte, Kaushalya (2024)
The glochidium larvae of the endangered freshwater pearl mussel, Margaritifera margaritifera infect the gills of suitable host fish and typically become encysted. Captive breeding has emerged as a crucial conservation measure for this species. Understanding the relationship between the larvae and host fish, particularly regarding the larvae growth and development during its parasitic phase, is essential to improve the efficiency of breeding programs. Thus, this study aimed to explore some key aspects of glochidia growth in its host fish, Atlantic salmon (Salmo salar), including the density-dependent growth of the larvae, variation in the cyst thickness and the relative cyst size of the encysted glochidia, and the growth differences between encysted and non-encysted glochidia. Further, this study aimed to test a new direct pipette method to infect host fish with different glochidia doses. To achieve these aims, Atlantic salmon were infected with River Simojoki M. margaritifera glochidia. During infection, glochidia were directly pipetted onto the gills of anesthetized fish. After three months, microscopic analysis of the fish gills was done to collect data on glochidia number, length, and cyst size from a subset of glochidia sampled from each gill arch. Results showed that the direct pipette infection method is effective for infecting fish with various doses of glochidia. There was a trend for a positive relationship between glochidia number and size. However, since the planned mass infection experiments to investigate density dependence failed for unknown reasons, a further study with a larger sample size of infected fish is needed to draw conclusions about the density-dependence of parasite growth. Host fish length affected significantly positively to glochidia cyst thickness. Some glochidia had no cysts, but there was no significant difference in their growth compared to the encysted ones. Overall, the question of positive density dependence between infra-population size and growth of M. margaritifera glochidia in Atlantic salmon remains open. However, the study provided new, valuable information about the parasitic stage of this endangered species—specifically cyst characteristics—in this fish-mussel association.